Fathers of the covenant - Ellison, Henry Leopold, 1903- (Exeter, UK Paternoster, 1978)
Includes bibliographical references and indexes.
Brethren writer.
Keywords: Bible. O.T. Genesis -- study and teaching; Bible. O.T. Exodus -- study and teaching